Characterization of the thermal performance of an outdoor telecommunication cabinet - Silva, Pedro Dinho da (2019)
This work describes the analysis of the thermal performance of an outdoor telecommunication cabinet (OTC) using the computational tool DesignBuilder. The simulation results are compared to the experimental data collected in real cabinet under normal operating conditions. The simulation results show that the air temperature predicted by the model is closer to the temperature measured experimentally inside the cabinet particularly when the weather data files of the computational model have a similar behavior to the actual weather data. Numerical studies show that the use of mechanical ventilation is effective in the extraction of heat generated inside the cabinet.